2023
DOI: 10.1002/ctm2.1361
|View full text |Cite
|
Sign up to set email alerts
|

METTL3‐stabilized super enhancers‐lncRNA SUCLG2‐AS1 mediates the formation of a long‐range chromatin loop between enhancers and promoters of SOX2 in metastasis and radiosensitivity of nasopharyngeal carcinoma

Xinyu Hu,
Jianfeng Wu,
Yong Feng
et al.

Abstract: BackgroundSuper enhancers (SE) play pivotal roles in cell identity and diseases occur including tumorigenesis. The depletion of SE‐associated lncRNA transcripts, also known as super‐lncRNA, causes the activity of SE to be dysregulated.MethodsWe screened and identified an elevated metastasis‐associated SE‐lncRNA SUCLG2‐AS1 in nasopharyngeal carcinoma (NPC) using RNA‐sequencing, real‐time quantitative polymerase chain reaction (RT‐qPCR) and bioinformatics. Western blotting, RT‐qPCR, methylated RNA immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Variations in Breast Cancer Patients (19). COX7A1 may connected with methylation and suppressed the viability of human non-small cell lung cancer cells via regulating autophagy (20)(21).The regulation of CPT2 was found downregulation in cancer tissue (22)(23).The downregulation of CPT2 promoted proliferation and inhibited apoptosis through p53 pathway in colorectal cancer (23).And CPT2 downregulation triggered stemness and oxaliplatin resistance in colorectal cancer via activating the ROS/Wnt/β-catenin-induced glycolytic metabolism (24).DLAT as an immunological and prognostic biomarker correlated with Prognosis, Chemoresistance, and Immune In ltration in variety of cancer (25)(26).A previous study revealed ECI2 was connected with epigenetic and genetic changes ECI2 in highgrade serous ovarian carcinoma (27).Downregulation of NDUFA1 and other oxidative phosphorylationrelated genes was a consistent feature of basal cell carcinoma(28).PPA2 was connected sudden cardiac death and the Mitochondrial Inorganic Pyrophosphatase (29).SUCLG2 participated in epigenetic expression and regulated cancer express (30).According this results,ATP6V1G2, ECI2, COX7A1, SUCLG2 was connected with epigenetic regulation.And the expression of ACOX1, PPA, NDUFA1 may regulate the mitochondria-related pathways in CRC.Therefore, according to drug sensitivity of TCGA and GEO MMRGs ,We found drug target prediction of the model's 10 genes, evaluated the potential therapeutic value of these genes, and screened for possible drug .…”
Section: Discussionmentioning
confidence: 96%
“…Variations in Breast Cancer Patients (19). COX7A1 may connected with methylation and suppressed the viability of human non-small cell lung cancer cells via regulating autophagy (20)(21).The regulation of CPT2 was found downregulation in cancer tissue (22)(23).The downregulation of CPT2 promoted proliferation and inhibited apoptosis through p53 pathway in colorectal cancer (23).And CPT2 downregulation triggered stemness and oxaliplatin resistance in colorectal cancer via activating the ROS/Wnt/β-catenin-induced glycolytic metabolism (24).DLAT as an immunological and prognostic biomarker correlated with Prognosis, Chemoresistance, and Immune In ltration in variety of cancer (25)(26).A previous study revealed ECI2 was connected with epigenetic and genetic changes ECI2 in highgrade serous ovarian carcinoma (27).Downregulation of NDUFA1 and other oxidative phosphorylationrelated genes was a consistent feature of basal cell carcinoma(28).PPA2 was connected sudden cardiac death and the Mitochondrial Inorganic Pyrophosphatase (29).SUCLG2 participated in epigenetic expression and regulated cancer express (30).According this results,ATP6V1G2, ECI2, COX7A1, SUCLG2 was connected with epigenetic regulation.And the expression of ACOX1, PPA, NDUFA1 may regulate the mitochondria-related pathways in CRC.Therefore, according to drug sensitivity of TCGA and GEO MMRGs ,We found drug target prediction of the model's 10 genes, evaluated the potential therapeutic value of these genes, and screened for possible drug .…”
Section: Discussionmentioning
confidence: 96%
“…AC005034.5 has been used to construct prognostic models in osteosarcoma [19] . SUCLG2-AS1 was found to be abnormally expressed in acute myeloid leukemia and a variety of tumors, affecting the development of nasopharyngeal carcinoma, triple-negative breast cancer, clear cell renal cell carcinoma and gastric cancer [20][21][22][23] . Moreover, AP003555.1 was identi ed and validated as a novel ferroptosis-related and oxidative stressrelated lncRNA and incorporated into a prognostic model for colon cancer [24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…In nasopharyngeal carcinoma radiotherapy, the demethyltransferase FTO promotes the expression of deubiquitylase (OTUB1) expression to counter ferroptosis and bolster the nasopharyngeal carcinoma radioresistance [ 51 ]. Additionally, METTL3 enables nasopharyngeal carcinoma cells to resist apoptosis after radiation by mediating the SUCLG2-AS1/CTCF/SOX2 axis [ 52 ]. Polo-like kinase 1 (PLK1) serves as a pivotal prognostic regulator in pancreatic cancer patients.…”
Section: M6a Rna Methylation In Radiation-induced Cellular Responses ...mentioning
confidence: 99%
“…It was reported that METTL3 mediates M6A modification of SUCLG2-AS1 transcript, a super enhancer associated lncRNA (SE-lncRNA), which is then recognized and stabilized by IGF2BP3. Consequently, SUCLG2-AS1 binds to the SE region of SOX2 to regulate SOX2 transcription, contributing to metastasis and radioresistance of nasopharyngeal carcinoma [ 52 ]. There is another report indicates that METTL3-mediated M6A modification involves in the prognosis and IR-induced alteration of cell cycle progressing of pancreatic cancer cells by targeting PLK1 mRNA 3’UTR [ 53 ].…”
Section: M6a Methylation In Rna During Cellular Responses To Cancer R...mentioning
confidence: 99%